2004
DOI: 10.1097/01.ccm.0000128549.72276.00
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in obstetric patients admitted to an Indian intensive care unit*

Abstract: Multiple organ failure is common in obstetric patients; mortality rate increases with increasing organ failure. APACHE II scores overpredict mortality rate. Standardized mortality ratio is lower in obstetric disorders than in medical disorders. Lack of prenatal care and delay in intensive care unit referral adversely affect outcome and are easily preventable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
114
2
19

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(154 citation statements)
references
References 21 publications
19
114
2
19
Order By: Relevance
“…Among the major causes of liver failure including viral hepatitis, acute fatty liver of pregnancy and HELLP syndrome, only viral hepatitis was associated with a poor maternal outcome. 41 …”
Section: Increased Risk Of Mortality In Pregnancy Due To Acute Viral mentioning
confidence: 99%
“…Among the major causes of liver failure including viral hepatitis, acute fatty liver of pregnancy and HELLP syndrome, only viral hepatitis was associated with a poor maternal outcome. 41 …”
Section: Increased Risk Of Mortality In Pregnancy Due To Acute Viral mentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Although some researchers found that APACHE II accurately predicted maternal death, 4,10 other researchers found that APACHE II overestimated maternal mortality rates 5 or, conversely, that it underestimated maternal mortality rates because of obstetric problems. 7 These differences may be due to higher mortality rates in some populations 7,9 or to overutilization of ICUs in less acutely ill populations 10 The only study in the United States to address this question used another scoring system, SAPS II. That study found that this system overestimated maternal mortality rates in all patients and specifically in patients who were admitted with obstetric indications but accurately predicted death in patients who were admitted for medical reasons.…”
Section: Commentmentioning
confidence: 99%
“…[1][2][3] Some studies have described the usefulness of ICU scoring systems in pregnant women, [4][5][6][7][8][9][10][11] but only 1 study has been based in the United States. 11 Gilbert et al 11 recently summarized the use of the Simplified Acute Physiologic Score (SAPS II) in 233 antepartum and postpartum patients who were admitted to a medical ICU in New Jersey from 1991 to 1998.…”
mentioning
confidence: 99%
“…Some of these are referred to as maternal near miss in case they narrowly survive death from such severe complications [5,6]. Both early recognition, detection and referral of potentially life threatening severe obstetric complications, and prompt access to safe, affordable basic and emergency obstetric care, are essential to reduce maternal morbidity and mortality [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…On this continuum are patients with severe obstetric complications, severe maternal morbidity (SMM), who develop organ or system dysfunction [3,4]. Some of these are referred to as maternal near miss in case they narrowly survive death from such severe complications [5,6].…”
Section: Introductionmentioning
confidence: 99%